Cryptococcal infections over a 15 year period at a tertiary facility & impact of guideline management. Issue 9 (13th July 2018) - Gassiep, Ian; Douglas, Joel; Emeto, Theophilus I.; Crawley, Katherine; Playford, Elliott G.
Summary: Cryptococcosis is an invasive fungal infection caused primarily by Cryptococcus neoformans and Cryptococcus gattii species, presenting predominantly as meningoencephalitis. The aim of this study is to assess all cryptococcal infections managed at our facility from 2001 to 2015 to determine incidence, risk factors, and comparison of outcomes prior to and following introduction of the 2010 Infectious Disease Society of America (IDSA) guidelines. Retrospective analysis of all patients diagnosed and treated for cryptococcal infection occurring between January 2001 and December 2015. Of 102 patients diagnosed with cryptococcal infection, 97 were eligible for study inclusion. There appears to be an overall increased incidence of cryptococcosis in both transplant and non‐transplant cohorts with a peak in 2015 of 6 transplant and 13 non‐transplant cases. In the meningitis cohort, 38/52 (73%) of identified isolates were C. neoformans, and 14/52 (27%) were C. gattii . Notably, 14/14 (100%) of C. gattii isolates were associated with meningitis, as compared to only 38/64 (59%) C. neoformans associated with meningitis ( P : .003). It appears that patients presenting with cough are less likely to have meningitis, 17/27 (63%), ( P : .005). When stratifying for culture positive meningitis lumbar puncture opening pressure, the median in the culture positive cohort was 31.5 cm H2 O compared with 15.5 cm H2 O ( P : .036).Multiple admissions were required prior to diagnosis in the majority of cases with only 18/72 (25%) diagnosed on 1st presentation. Postguideline mortality has improved from 15% to 6.1% ( P : .046). Cryptococcal infection remains relatively uncommon, but there appears to be an increasing trend in incidence. Overall mortality is relatively low and has improved since introduction of the 2010 IDSA guidelines.